(untitled) (Research, Society and Development, 2022)
Currently, much is discussed about the important theme of resilient cities, which according to the United Nations - UN (2018), are those that have the capacity of systems, societies, or communities to cope with the risks they are exposed to, having resilience to hazards, accommodation, absorption, adaptation, transformation, and recovery from the effects suffered in a timely and efficient manner, including the preservation and restoration of vital basic structures and functions through risk management. The study aims to highlight the importance of cities increasingly becoming resilient by listing the main steps to be followed by city managers, which are based on the UN’s Ten Resilience Building Principles for achieving resilience. The research has a basic, exploratory, and qualitative typology, followed by a Literature Review that constitutes the process of searching, analyzing, and describing a topic of knowledge, with the objective of identifying the steps to achieve resilience. It explored national and international literature, scientific articles, national and international agencies, to identify the steps necessary to build resilience. In view of the study carried out, the adherence to the UN’s Ten Principles for Building Resilience, with the effectiveness of the important steps in each principle, was indicated as the most appropriate for building resilience, and can be used by public managers for the solidification of sustainable development and the achievement of resilience.